Reconfigurable Three-Switch Leg Multi-Port Boost Inverters With Novel Modulation Schemes for Hybrid DC/AC Microgrid Systems - M. Rama Narayana Reddy; B. Dastagiri Reddy; Prajof Prabhakaran; Andrii Chub; Samir Kouro (IEEE Access)
This paper proposes reconfigurable single-stage three-switch leg multi-port boost inverters (TSLMPBIs) that feature novel hybrid modulation schemes for hybrid DC/AC microgrid system applications. The TSLMPBI topologies are designed to accommodate various configurations, including two DC ports with two AC ports, three DC ports with one AC port, and three DC ports with two AC ports, tailored for different applications. A hybrid modulation scheme was proposed, dynamically adapted to the configuration of DC and AC ports, facilitating seamless boost and dual inversion operations or combined boost, buck, and inversion functionalities within a single converter. The AC ports operate at various voltages, frequencies, and phases, while the DC ports support multiple voltage levels. The proposed control modulation scheme effectively addresses crossover issues in modulation signals, resulting in enhanced AC voltage gain, improved DC bus utilization, and optimized power transfer among DC and AC ports. Additionally, these topologies reduce active switch count compared to state-of-the-art designs, even with increased ports. To validate the performance of the proposed TSLMPBI and its control modulation scheme, a 500 W laboratory prototype was developed, and experimental results under various operating scenarios were presented and analyzed.